Partial Substitution of Edible Mealworms for Corn Flour in a Plant-based Food Nugget - Adrianna E. Gonnella; David A. Olds (Undergraduate Research Journal for the Human Sciences, 2025)
The purpose of this study was to determine an acceptable level of mealworm powder (MW) substituted for corn flour (CF) to provide a higher level of protein in a plant-based food nugget. Data collection included sensory analysis evaluations and post-consumption survey responses from 44 untrained panelists. Mean sensory evaluation scores of nuggets for each of the five characteristics (crust color, interior color, texture, flavor, and aftertaste) across the four groups (0% MW, 25% MW, 50% MW, and 75% MW substituted for CF, respectively) decreased in acceptability with each percentage increase of MW substituted for CF. Post-consumption survey responses immediately following sensory analysis indicated panelists’ increased interest in eating insects. Results of this study indicated that a substitution of up to 25% mealworm powder for corn flour was an acceptable method to provide a higher level of insect protein in a plant-based nugget. Further research into insect protein substitution is recommended.
Keywords: insect protein; sensory analysis; sustainability; nutrition